Etnography and Multicultural Dynamics Communication of Jakarta Community - Syaiful Rohim; Edi Sukardi; Lina Yulinda (Universitas Prof. Dr. Moestopo (Beragama), 2023)
Betawi culture has been formed through a long process, but in fact the culture is displaced. One of the things that make Betawi tribe still exist and can be recognized is because of the assimilation process of various tribes in Indonesia. Betawi ethnic is created by the various arts of culture, language, and humans. The simplicity factors of the cultures make Betawi ethnic is accepted in all levels of Indonesian society. Intercultural communication patterns of the language which is used by Betawi people, have cultural backgrounds that affect their daily language. The multi-ethnic populations give a nuance of the heterogeneous city life in Batavia. This study uses a qualitative approach, the results of this research shows that the patterns and the cultures of Betawi produce the structure, the language and Betawi culture which is simple or easy to say and tends to “ceplas ceplos” in articulation words. Beside that it is found the communication culture of Betawi character which is shown from the openness attitude, family spirit, cooperation and respect for other people's cultures.